CHEMICAL COMPOSITION OF MINERALS AND CLASSIFICATION - Kalıknazarova Amangul; Qutimova Gulnara; Tlemuratova Gulbahar; Baymuratova Guljan (Sciental Journals Publishing, 2025)
Production of Minerals. Minerals are mainly under certain thermodynamic conditions. It will be fruitful. According to the current information, the main part of the available minerals originates in the inner part of the earth's crust, in the gradual crystallization of magma (melt) or its products (gas, steam, boiling water solutions, etc.) with the surrounding rocks. Resulting from mutual reaction. They become secondary minerals in the atmosphere, biosphere and hydrosphere. Such natural compounds formed in the upper part of the compounds are called exogenous minerals. Exogenous minerals, in turn, are formed as a result of the subsidence of the Earth's crust or the rise of magma, tuff as a result of the action of moving to another state. They do not survive in such conditions under the influence of temperature and pressure, it turns into metamorphic minerals adapted to new conditions.
Keywords: Mineral, chemical, element.